The role of imaging in diagnosing neuromyelitis optica spectrum disorder - Matthews, L; Palace, J (2013)
Early identification of neuromyelitis optica allows aggressive acute and prophylactic relapse management aimed at preventing disability. Since the discovery of pathogenic aquaporin-4 antibodies the neuromyelitis optica spectrum has widened significantly: brain lesions no longer preclude the diagnosis and there are reports of symptoms of cerebral origin presenting as the first manifestation of the condition, prior to optic nerve or spinal cord disease. Defining antibody negative neuromyelitis optica, and distinguishing it from other inflammatory disorders such as multiple sclerosis can therefore be a challenge. In this review we discuss the role of conventional imaging in the diagnosis of neuromyelitis optica, and the scope of quantitative MRI modalities to identify more specific pathophysiological features to aid in the differentiation from other conditions and assess treatment response. © 2013 Elsevier B.V. All rights reserved.